Legal Issues Regarding Surrogate Motherhood in Greece - Συμεωνίδου - Καστανίδου (Elisavet Symeonidou – Kastanidou), Ελισσάβετ (Bioethica, 2018)
The aim of this study is to highlight critical legal issues related to surrogate motherhood and to propose solutions to improve the current legal framework. In particular, it refers to the need for a final court decision to apply surrogate motherhood, the preconditions examined by the court to grant the relevant license, the meaning of the term "medically impossible to get pregnant", the content of the agreement between the applicants and the surrogate mother and finally the preconditions for considering a woman suitable for becoming a surrogate mother, with an emphasis on age-limits.